9514 1404 393
Answer:
5) 729, an=3^n, a[1]=3; a[n]=3·a[n-1]
6) 1792, an=7(4^(n-1)), a[1]=7; a[n]=4·a[n-1]
Step-by-step explanation:
The next term of a geometric sequence is the last term multiplied by the common ratio. (This is the basis of the recursive formula.)
The Explicit Rule is ...
![a_n=a_1\cdot r^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1%5Ccdot%20r%5E%7Bn-1%7D)
for first term a₁ and common ratio r.
The Recursive Rule is ...
a[1] = a₁
a[n] = r·a[n-1]
__
5. First term is a₁ = 3; common ratio is r = 9/3 = 3.
Next term: 243×3 = 729
Explicit rule: an = 3·3^(n-1) = 3^n
Recursive rule: a[1] = 3; a[n] = 3·a[n-1]
__
6. First term is a₁ = 7; common ratio is r = 28/7 = 4.
Next term: 448×4 = 1792
Explicit rule: an = 7·4^(n-1)
Recursive rule: a[1] = 7; a[n] = 4·a[n-1]
7 1/3
I think this is it, i would like for u to get a second opinion.
Answer:
![log_2(10)](https://tex.z-dn.net/?f=log_2%2810%29)
<h3>how to find</h3>
Simplify the equation using logarithms.
<h3>part 1</h3>
![2^3x=10](https://tex.z-dn.net/?f=2%5E3x%3D10)
![log_1_0(2^3x)=log_1_0(10)](https://tex.z-dn.net/?f=log_1_0%282%5E3x%29%3Dlog_1_0%2810%29)
log rule ⇩
![log_a(x^y)=y*log_a(x)](https://tex.z-dn.net/?f=log_a%28x%5Ey%29%3Dy%2Alog_a%28x%29)
move exponent out of log.
![x*log_1_0(2)=log_1_0(10)](https://tex.z-dn.net/?f=x%2Alog_1_0%282%29%3Dlog_1_0%2810%29)
<h3>part 2</h3>
<em>isolate variable further</em>
![x*log_1_0(2)=log_1_0(10)](https://tex.z-dn.net/?f=x%2Alog_1_0%282%29%3Dlog_1_0%2810%29)
![x=\frac{log_{10}(10)}{log_{10}(2)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7Blog_%7B10%7D%2810%29%7D%7Blog_%7B10%7D%282%29%7D)
formula for combining logs. ⇩
![\frac {log_b(x)}{log_b(a)}=log_a(x)](https://tex.z-dn.net/?f=%5Cfrac%20%7Blog_b%28x%29%7D%7Blog_b%28a%29%7D%3Dlog_a%28x%29)
the result ⇩
![x=log_2(10)](https://tex.z-dn.net/?f=x%3Dlog_2%2810%29)
Answer:
i think the 2nd one
Step-by-step explanation:
Answer:
slope = m = (0--3)/(14--4) = 3/18 = 1/6
y=mx + b
y =(1/6)x + b
0= (1/6)14 + b
b = - 14/6 = - 7/3
y = (1/6)x - 7/3
or
6y-x = -14
Step-by-step explanation: